Trade Relations between Ancient Egypt and Phoenicia - khier, ameur (Journal of Social Sciences and Humanities, 2016)
The Near East witnessed the emergence of the first civilizations, from which urbanism began and lifestyles evolved through the transition from agricultural stability and fixed settlement in fertile regions to global openness. In this region, the elements of civilization culminated in their highest forms. Among the most significant civilizations that played a role in human renaissance were Phoenicia and Egypt, serving as contact zones between Africa and Asia. The subject of "Trade" was chosen as a model for relations between Egypt and Phoenicia because trade significantly contributed to fostering harmony between societies based on mutual benefit and facilitating cultural communication across various fields. Furthermore, it served as a means of wealth accumulation, leading to interaction between peoples and the eventual construction of contemporary human civilization.